2016
DOI: 10.1021/acs.inorgchem.6b01804
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Subsequent Reactivity of an Fe-Peroxo Porphyrin Generated by Electrochemical Reductive Activation of O2

Abstract: Reductive activation of O is achieved by using the [Fe(FTPP)Cl] (FTPP = 5,10,15,20-tetrakis(pentafluorophenyl) porphyrinate) porphyrin through electrochemical reduction of the [Fe(FTPP)(O)] superoxo complex. Formation of the [Fe(FTPP)(OO)] peroxo species is monitored by using low-temperature electronic absorption spectroscopy, electron paramagnetic resonance, and cyclic voltammetry. Its subsequent protonation to yield the [Fe(FTPP)(OOH)] hydroperoxo intermediate is probed using low-temperature electronic absor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 37 publications
7
32
0
Order By: Relevance
“…The best fit of the experimental LSVs at G and the C UME for Fe(F 20 TPP) is obtained for K O 2 = 25 AE 10 s À1 , a value comparable but lower to previous estimate based only on the analysis of the CVs at G (see Section 4, SI), [14] and k d = 1 AE 0.3 s À1 as shown in Figure 3 A,B. k d is 20 times higher than the apparent Fe III (OO 2À ) decomposition rate constant determined by the thin-layer spectroelectrochemical study at 253 K (Section 2, SI), a difference that could be accounted for by the 40 K temperature difference between the two experiments.…”
supporting
confidence: 45%
See 2 more Smart Citations
“…The best fit of the experimental LSVs at G and the C UME for Fe(F 20 TPP) is obtained for K O 2 = 25 AE 10 s À1 , a value comparable but lower to previous estimate based only on the analysis of the CVs at G (see Section 4, SI), [14] and k d = 1 AE 0.3 s À1 as shown in Figure 3 A,B. k d is 20 times higher than the apparent Fe III (OO 2À ) decomposition rate constant determined by the thin-layer spectroelectrochemical study at 253 K (Section 2, SI), a difference that could be accounted for by the 40 K temperature difference between the two experiments.…”
supporting
confidence: 45%
“…We focus here on the first intermediate produced in nonacidic medium, the Fe III (OO 2À ) (peroxo) adduct, for three porphyrins showing, based on earlier work, [7,14]…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This clearly reflects the harder Lewis acidity of the Fe II center when it is coordinated to the electron‐withdrawing L 4 2 NO 2 ligand. As stated above, such a property is required for a more efficient coordination of dioxygen to the Fe II center and an easier subsequent activation , …”
Section: Resultsmentioning
confidence: 99%
“…A thorough mechanistic investigation of this reaction through cyclic voltammetry revealed that the coordination of O 2 to an Fe II center, which leads to a putative Fe III –superoxo intermediate, is disfavored with this family of polydentate aza ligands . To develop more reactive Fe II precursors that facilitate the formation of the Fe III –superoxo intermediate and avoid the reduction of the latter, it appeared crucial to make the metal center more Lewis acidic , . Herein, we report the synthesis, characterization, and stability studies of Fe II complexes prepared with the ligand N , N′ ‐dimethyl‐ N , N′ ‐bis(4‐nitropyridin‐2‐ylmethyl)ethane‐1,2‐diamine ( L 4 2 NO 2 ), in which the pyridyl rings are functionalized with electron‐withdrawing para ‐nitro groups to provide the desired electronic effects without impacting the accessibility to the metal center.…”
Section: Introductionmentioning
confidence: 99%